INVESTIGASI HUBUNGAN IRADIASI MATAHARI DENGAN THD PADA INVERTER PLTS UNIVERSITAS UDAYANA - Anak Agung Istri Pandawani; Cok. Gede Indra Partha; I Wayan Sukerayasa (Program Studi Teknik Elektro UNUD, 2023)
Solar Power System as one of the uses of renewable energy whose use is very widespread and one of its implementations is on the roof of the DH Electrical Engineering Building of Udayana University. The increase in the use of solar power plants is followed by an increase in the use of switching equipment such as inverters that produce harmonic distortions and affect the power quality of the electrical system. This investigation aims to analyze the condition of THD in inverters and analyze factors related to THD in inverters, one of which is solar irradiation. THDi output inverter inverter PLTS Udayana University exceeds the permitted IEEE 519-2014 standard, which is a maximum of 5%. The relationship that occurs between irradiation and the inverter of Udayana University PLTS when connected to the load is inversely proportional so that when irradiation is high during the day, the THDi output of the inverter will be low and vice versa in the evening.